Fighting insect damage to legumes - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Insect pests of tropical food legumes edited by S R Singh 451 pp, 1990 ISBN 0 471 923907 Available from CTA